ROLE OF OXIDATIVE STRESS IN RENAL ARTERY ATHEROSCLEROSIS: A CLINICAL AND EXPERIMENTAL STUDY - Nazarova Nigina Otabek qizi; Xasanova Malika Axramovna; Raximova Gulsum Po‘latboy qizi; Madazimova Dilruh Xayotjonovna (Modern American Journals, 2025)
Renal artery Atherosclerosis (RAА) is a major cause of secondary hypertension and ischemic nephropathy, often associated with atherosclerotic vascular disease. The condition leads to reduced renal perfusion, activation of the renin-angiotensin-aldosterone system (RAAS), and progressive kidney dysfunction. In recent years, oxidative stress has emerged as a crucial mechanism underlying the pathophysiology of RAА. Oxidative stress refers to an imbalance between the production of reactive oxygen species (ROS) and the body's antioxidant defenses, resulting in cellular damage. In the context of RAА, increased ROS production contributes to endothelial dysfunction, vascular remodeling, hypoxia, and renal fibrosis. While these mechanisms have been well-characterized in animal models, there is growing clinical evidence supporting the role of oxidative stress in human RAА. Understanding these mechanisms may help guide novel therapeutic approaches to improve renal outcomes in affected patients.